New soluble angiopoietin analog of Hepta‐ANG1 prevents pathological vascular leakage - Liu, Pan; Ryczko, Michael; Xie, Xinfang; Baardsnes, Jason; Lord‐Dufour, Simon; Duroche, Yves; Hicks, Emily Anne; Taiyab, Aftab; Sheardown, Heather; Quaggin, Susan E; Jin, Jing (Biotechnology and bioengineering, 2021)
Vascular leak is a key driver of organ injury in diseases, and strategies that reduce enhanced permeability and vascular inflammation are promising therapeutic targets. Activation of the angiopoietin-1 (ANG1)-Tie2 tyrosine kinase signaling pathway is an important regulator of vascular quiescence. Here we describe the design and construction of a new soluble ANG1 mimetic that is a potent activator of endothelial Tie2 in vitro and in vivo. Using a chimeric fusion strategy, we replaced the extracellular matrix (ECM) binding and oligomerization domain of ANG1 with a heptameric scaffold derived from the C-terminus of serum complement protein C4-binding protein α. We refer to this new fusion protein biologic as Hepta-ANG1, which forms a stable heptamer and induces Tie2 phosphorylation in cultured cells, and in the lung following intravenous injection of mice. Injection of Hepta-ANG1 ameliorates vascular endothelial growth factor- and lipopolysaccharide-induced vascular leakage, in keeping with the known functions of Angpt1-Tie2 in maintaining quiescent vascular stability. The new Hepta-ANG1 fusion is easy to produce and displays remarkable stability with high multimericity that can potently activate Tie2. It could be a new candidate ANG1 mimetic therapy for treatments of inflammatory vascular leak, such as acute respiratory distress syndrome and sepsis.